Perkembangan Ritual Adat Mangongkal Holi Batak Toba dalam Kekristenan di Tanah Batak - Firman Oktavianus Hutagaol; Iky Sumarthita P. Prayitno (Universitas Negeri Medan, 2020)
This paper is the result of observations and analysis of religious sociology on the traditional mangongkal holi rituals in Pahae Julu, North Tapanuli Regency, North Sumatra. This paper aims to explore and explain the social and cultural values contained in this traditional ritual. This ritual survives and adheres to the Toba Batak tribe even though its implementation has been adapted to the teachings of Christianity prevailing in the Batak Land. Some of the social and cultural values contained in the ritual still survive and are important for the Toba Batak people. To approach this problem, theoretical references from Emile Durkheim and Max Weber are used. Data was collected through literature studies, interviews, and direct observations of these traditional rituals in the Pahae Julu area, as well as qualitative analysis. This paper concludes that this traditional ritual contains mechanical solidarity and the role of the charismatic ritual leader for the Batak people.